Health care workers' knowledge on identification, management and treatment of snakebite cases in rural Malawi: A descriptive study - Moses Banda Aron; Chiyembekezo Kachimanga; Benno Kreuels; Bright Mailosi; Clara Sambani; Beatrice Lydia Matanje; Joerg Blessmann; Mwayi Chunga; Grace Momba; Enoch Ndarama; Dzinkambani Moffat Kambalame; Emilia Connolly; et al. (Public Library of Science (PLoS), 2022)
Snakebite envenoming remains a public health threat in many African countries, including Malawi. However, there is a shortage of literature on the knowledge of Health Care Workers (HCWs) and the prevalence of snakebite cases in Malawi. We interviewed HCWs in Neno District to assess their knowledge of snake identification and management of snakebites. We further reviewed patient registers from 2018 to 2021 in all 15 health facilities in the district. We used descriptive statistics to characterize the survey population, knowledge, snake antivenom (SAV) administration, and snake identification. Using "shapefiles" from Open Street Maps, we mapped villages with snakebite cases. Of the 105 HCWs interviewed, 58% were males, and 60% had worked for less than five years. The majority (n = 93, 89%) reported that snakebite envenoming was a problem in the district. Among the clinicians, 42% said they had prescribed SAV previously, while among nurses, only 26% had ever administered SAV. There were discrepancies among clinicians regarding the dosing of snake antivenom. Significant gaps in knowledge also existed regarding snake identification. While two-thirds of HCWs could correctly name and identify venomous snake species, most (> 90%) failed for non-venomous snakes. Most (n = 100, 95%) reported that snakebite victims visit traditional healers more than the hospital. Between 2018 and 2021, the Neno District registered 185 snakebites with a yearly average of 36 cases per 100,000 population. Fifty-two percent (n = 97) were treated as an inpatient; of these cases, 72% were discharged in less than three days, and two died. More snakebite cases were recorded in the eastern part of the district. Significant knowledge gaps exist among HCWs in Neno regarding prescription and administration of SAV and snake identification, which likely challenges the quality of services offered to snakebite victims. Author summary Knowledge about management of snakebite envenoming and the availability of effective antivenom against the relevant venomous snake species are a "sine qua non" for a favorable outcome. There is no published literature addressing snakebite incidence and knowledge of health care workers in management of snakebite patients in Malawi. The present study investigated the number of snakebite cases managed at health facilities in Neno District in Southern Malawi between 2018 and 2021 and evaluated knowledge of health care workers about management of snakebite envenoming and the local snake fauna. Although the majority of interviewees considered snakebite a major problem, their knowledge in management of snakebite cases was not sufficient. Incidence of healthcare encounters due to snakebites in Neno District was calculated at 36 per 100,000 population. This is most likely a significant underestimation as treatment of victims by traditional healers in their village seems to be common. The study shows that further training of health care workers and more data on the epidemiology and clinical consequences of snakebites in Malawi are urgently needed.